Implementation of a Community-Based Approach to Dementia Care in England: Understanding the Experiences of Staff. Issue 43 (27th May 2017) - Brookes, Nadia
ABSTRACT: Given the increasing numbers of people living with dementia, it is imperative that new, practical solutions are found to the issues faced by this group of people and their families. This article draws on findings from a qualitative study that explored the implementation of a community-based project to support people living with dementia in one local area in England. This approach has different names; in the United Kingdom it is Shared Lives or adult placement, which would be most comparable to family care in Europe and adult foster care in the United States. Interviews were conducted with 14 staff connected to the Shared Lives project. Interview data were coded using the normalization process theory constructs of coherence, cognitive participation, and collective action. Supportive program factors identified were a dedicated staff member and resources, and the availability of specialist knowledge and skills. Detriments to program success included lack of understanding about the service, perceptions it was a poor fit with existing practice, and wider organizational issues that negatively affected normalization of the intervention. Suggestions for future research go beyond staff opinions, stressing the importance of using a wider range of stakeholders and incorporating measurement of outcomes for people using the service.